1999
DOI: 10.1016/s0014-5793(99)00600-6
|View full text |Cite
|
Sign up to set email alerts
|

Calcium release from InsP3‐sensitive internal stores initiates action potential in Chara

Abstract: Neomycin and U73122 are known to suppress inositol 1,4,5-trisphosphate (InsP3) production by inhibition of phospholipase C. We studied the effects of these inhibitors on the excitatory currents, Iex, in Chara corallina under voltage-clamp conditions. Computer simulations of the experimental effects by a minimum model for the excitatory reaction pathway allow the assignment of the inhibitory effects to one specific reaction step, i.e. the release of Ca2+ from InsP3-sensitive internal stores. In contrast, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 42 publications
2
44
1
Order By: Relevance
“…These findings suggested the involvement of a long-lived signaling molecule, which is produced in a voltage-dependent manner and is able to mobilize Ca 2+ internal stores. This interpretation is in good agreement with other experiments, which had already suggested from independent approaches that electrical excitation in Chara is due to a mobilization of Ca 2+ from internal stores , Thiel & Dityatev, 1998, and may be mediated by the second messenger inositol 1,4,5-trisphosphate (IP 3 ) (Thiel, MacRobbie & Henke, 1990;Biskup, Gradmann & Thiel, 1999;Wacke & Thiel, 2001).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings suggested the involvement of a long-lived signaling molecule, which is produced in a voltage-dependent manner and is able to mobilize Ca 2+ internal stores. This interpretation is in good agreement with other experiments, which had already suggested from independent approaches that electrical excitation in Chara is due to a mobilization of Ca 2+ from internal stores , Thiel & Dityatev, 1998, and may be mediated by the second messenger inositol 1,4,5-trisphosphate (IP 3 ) (Thiel, MacRobbie & Henke, 1990;Biskup, Gradmann & Thiel, 1999;Wacke & Thiel, 2001).…”
Section: Introductionsupporting
confidence: 92%
“…These reveal that plants possess the key proteins and mechanisms for a stimulus-induced and IP 3 -mediated mobilization of Ca 2+ from internal stores (Sanders, Brownlee & Harper, 1999;Reddy, 2001). Also Chara cells most likely have such a signalling system, because it was shown that electrophoretic injection of IP 3 triggered membrane excitation (Thiel, MacRobbie & Hanke, 1990), while inhibition of phospholipase C abolished excitability of these cells (Biskup et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The source of Ca 2+ ions entering the cytoplasm in an early phase of the AP is still a matter of debate. Either external 41 or internal stores 42 are postulated as being responsible for Ca 2+ fluxes. Here, we show that lanthanum, a rather unspecific Ca 2+ channel blocker, completely inhibits APs in Physcomitrella cells.…”
Section: Discussionmentioning
confidence: 99%
“…An essential mechanism for AP generation is the activation of the voltage-dependent ion channels. In plants, changes in ion permeability during APs are largely explained on the basis of a transient activation of Ca 2+ channel first, and Cl -channel next, both responsible for the depolarization phase of AP (Kourie 1994, Thiel and Dityatev 1998, Biskup et al 1999, Wacke and Thiel 2001.…”
Section: Introductionmentioning
confidence: 99%